The Impact of Timing of Stent Removal on the Incidence of UTI, Recurrence, Symptomatology, Resistance, and Hospitalization in Renal Transplant Recipients. (3rd July 2021) - Arabi, Ziad; Al Thiab, Khalefa; Altheaby, Abdulrahman; Tawhari, Mohammed; Aboalsamh, Ghaleb; Almarastani, Mohamad; Kashkoush, Samy; Shaheen, Mohammed F; Altamimi, Abdulrahman; Alnajjar, Lina; Alhussein, Rawan; Almuhiteb, Raghad; et al.
Abstract : Purpose . To evaluate the impact of early (<3 weeks) versus late (>3 weeks) urinary stent removal on urinary tract infections (UTIs) post renal transplantation. Methods . A retrospective study was performed including all adult renal transplants who were transplanted between January 2017 and May 2020 with a minimum of 6-month follow-up at King Abdulaziz Medical City, Riyadh, Saudi Arabia. Results . A total of 279 kidney recipients included in the study were stratified into 114 in the early stent removal group (ESR) and 165 in the late stent removal group (LSR). Mean age was 43.4 ± 15.8; women: n : 114, 40.90%; and deceased donor transplant: n : 55, 19.70%. Mean stent removal time was 35.3 ± 28.0 days posttransplant (14.1 ± 4.6 days in the ESR versus 49.9 ± 28.1 days in LSR, p < 0.001 ). Seventy-four UTIs were diagnosed while the stents were in vivo or up to two weeks after the stent removal "UTIs related to the stent" ( n  = 20, 17.5% in ESR versus n  = 54, 32.7% in LSR; p = 0.006 ). By six months after transplantation, there were 97 UTIs ( n  = 36, 31.6% UTIs in ESR versus n  = 61, 37% in LSR; p = 0.373 ). Compared with UTIs diagnosed after stent removal, UTIs diagnosed while the stent was still in vivo tended to be complicated (17.9% versus 4.9%, p : 0.019), recurrent (66.1% versus 46.3%; p : 0.063), associated with bacteremia (10.7% versus 0%; p : 0.019), and requiring hospitalization (61% versus 24%, p : 0.024). Early stent removal decreased the need for expedited stent removal due to UTI reasons (rate of UTIs before stent removal) ( n  = 11, 9% in the early group versus n  = 45, 27% in the late group; p = 0.001 ). The effect on the rate of multidrug-resistant organisms (MDRO) was less clear (33% versus 47%, p : 0.205). Early stent removal was associated with a statistically significant reduction in the incidence of UTIs related to the stent (HR = 0.505, 95% CI: 0.302-0.844, p = 0.009 ) without increasing the incidence of urological complications. Removing the stent before 21 days posttransplantation decreased UTIs related to stent (aOR: 0.403, CI: 0.218-0.744). Removing the stent before 14 days may even further decrease the risk of UTIs (aOR: 0.311, CI: 0.035- 2.726). Conclusion . Early ureteric stent removal defined as less than 21 days post renal transplantation reduced the incidence of UTIs related to stent without increasing the incidence of urological complications. UTIs occurring while the ureteric stent still in vivo were notably associated with bacteremia and hospitalization. A randomized trial will be required to further determine the best timing for stent removal.